Regarding the issue of determining the deceleration of a two-axle vehicle with a damaged brake system - Leontiev, Dmytro; Klymenko, Valeriy; Aloksa, Mykola; Sylchenko, Mykola; Леонтьєв, Дмитро Миколайович; Клименко, Валерій Іванович; Альокса, Микола Миколайович; Сильченко, Микола Миколайович (Харківський національний автомобільно-дорожній університет, 2022)
Problem. During the study of the circumstances of the occurrence of road accidents, the experts of the automotive technical expertise face a problem of choosing the mathematical model for determining the deceleration of a two-axle vehicle with a faulty working brake system. The search for a universal method for calculating the amount of deceleration of a two-axle vehicle with a faulty working brake system is an urgent scientific task that will expand the understanding of the physical processes on which the provisions of the theory of the car are based. Goal. The aim of the work is to generalize theoretical research to determine the deceleration of a two-axle vehicle with a faulty working brake system. Methodology. The approaches adopted in the work to solve this goal are based on the analysis of methods for determining the deceleration of two-axle wheeled vehicles. Results. The obtained calculated values of deceleration of a two-axle wheeled vehicle with different external factors allowed to establish the features of the use of different methods in the practice of automotive technical expertise. It is established that taking into account the angle of the road surface towards the roadside and taking into account the coefficient of resistance of car tires can change the extent of deceleration of a two-axle wheeled vehicle with a faulty service brake system. Originality. The proposed universal method for determining the deceleration of a two-axle wheeled vehicle with a faulty working brake system, allows to take into account the influence of rolling resistance of tires and the angle of inclination of the road surface towards the roadside when studying the circumstances of a traffic accident. Practical value. The results obtained can be recommended in the practice of automotive technical expertise or in research related to determining the braking performance of two-axle wheeled vehicles.
Щодо питання визначення уповільнення двовісного транспортного засобу з несправною робочою гальмовою системою
Keywords: braking efficiency; braking rate; vehicle deceleration; brake system malfunction; braking process modeling; ефективність гальмування; коефіцієнт гальмування; уповільнення транспортного засобу; несправність гальмової системи; моделювання процесу гальмування; 629.01; 10.30977/AT.2019-8342.2022.50.0.03